PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA BURSA EFEK INDONESIA - Tri Kartika Pertiwi; Rizki Ayu Dian Mega Dewati (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
Along with the technological advances support, companies are always required to innovate and compete in global conditions like this. Every company must have a short-term goal of maximizing profit. This study aims to test, prove, and analyze the effect of Profitability and Dividend Policy as intervening variables on Firm Value. This study uses secondary data in the form of financial statement data. The population applied is 22 companies, and the sample used is 110 Food and Beverage Sub-Sector Companies on the Indonesia Stock Exchange for five years, using the purposive sampling method. This study uses path analysis using SPSS version 25. The results of this study indicate that: profitability has a positive and significant effect on firm value, profitability has a negative and significant effect on dividend policy, dividend policy has a positive and significant effect on firm value, dividend policy mediates the indirect effect between profitability and firm value in food and beverage companies